2018
DOI: 10.31532/interdiscipeducpsychol.2.1.003
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-disciplinary Empirical Investigation of Active Learning Classroom’s Effects on Student Learning

Abstract: These plans recognized that technology could be a powerful tool to assist learning and urged all education stakeholders to use technology effectively to improve American education. To better incorporate technology into education, many institutions in higher education are investing in redesigning traditional classrooms (TCs) into technology-rich active learning classrooms (ALCs), with the expectation of making an influential impact on student learning (Hunley & Schaller, 2006). These ALCs typically

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Our previous analysis examined the differences in mean scores of grades earned in the ALC and TCs, 19 but failed to explore how different variables influenced the final grades in different learning environments. To find out the correlations among students' demographics, prior academic performance variables, and final grades in each type of classroom setting, we performed separate multiple regression analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous analysis examined the differences in mean scores of grades earned in the ALC and TCs, 19 but failed to explore how different variables influenced the final grades in different learning environments. To find out the correlations among students' demographics, prior academic performance variables, and final grades in each type of classroom setting, we performed separate multiple regression analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, as flipped classroom setting is new to the teaching staff and students, the full potential of it might not have been reached. Improved experience with flipped classroom setting might lead to a more promising result [ 16 ]. Nevertheless, our findings agree with a recent systematic review that showed the flipped classroom was as effective as the traditional teaching method [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although our students used both the traditional lecture hall and the CUBE during their five academic years, they utilised the traditional lecture hall more frequently. Familiarity of the students and the teachers with the new learning space may influence the experience of users (Gordy et al, 2018). Nevertheless, there is a need to upgrade the lecture hall to be a technology-rich learning environment while maintaining the features of a traditional lecture hall that the students preferred.…”
Section: Discussionmentioning
confidence: 99%
“…However, the active learning classroom also affects students with sensory and technique challenges i.e., the students can be distracted by the enhanced sensory stimulation and it requires students to have the technical skills to follow the class (Gordy et al, 2019). Although students preferred an active learning classroom, the advantage was not reflected in terms of improvement in the examination grades (Gordy et al, 2018). However, the duration of use and familiarity of the students and the teachers with the new learning environment is another influencing factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation